Development of learning video comparison using Palembang jumputan context to determine students' mathematical reasoning - Nabila, Siti; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi (Jurnal Elemen, 2024)
The importance of learning videos on comparison materials in the context of Palembang jumputan fabric as a starting point for learning so that students have good mathematical reasoning ability. The purpose of this research is to produce a learning video on comparison using the context of Palembang jumputan fabric that is valid and practical and to determine the potential effect of using a learning video on comparison using the context of Palembang jumputan fabric on students' mathematical reasoning ability. This research uses the Pendidikan Matematika Realistik Indonesia (PMRI) and collaborative learning approaches. This type of research is a design research type of development study. The subjects of this study were 37 seventh-grade students at Srijaya Negara Junior High School, Palembang. The data collection techniques were observation, tests, and interviews, which were analyzed descriptively. This research produced a learning video on comparison material using the context of Palembang jumputan fabric that was valid and practical, and the potential effect of using learning videos on students' mathematical reasoning skills was classified as good, with an average value of 67.52. Using learning videos on comparison materials in the context of Palembang jumputan fabrics makes students' mathematical reasoning skills classified as good.